Emerging Biosensing Technologies for the Diagnostics of Viral Infectious Diseases (Adv. Mater. 30/2022). Issue 30 (27th July 2022) - Kabay, Gözde; DeCastro, Jonalyn; Altay, Alara; Smith, Kasey; Lu, Hsiang‐Wei; Capossela, Antonia McDonnell; Moarefian, Maryam; Aran, Kiana; Dincer, Can
Abstract : Biosensors The speed of innovation in the development, commercialization, and implementation of new technologies for infectious disease diagnostics has enabled humans to better combat the COVID‐19 pandemic. In article number 2201085, Kiana Aran, Can Dincer, and co‐workers highlight the development of various novel and reimagined multiomic sensing technologies to address the gaps in testing and surveillance for future outbreaks of coronaviruses and other infectious diseases.